Penggunaan Metode Demonstrasi Dalam Peningkatan Pemahaman Siswa Pada Pembelajaran PAI Materi Tata Cara Perawatan Jenazah - Safi'i, Muhammad; Satriah, Satriah; Tauhid, Moh. (JURNAL ILMU PENDIDIKAN & SOSIAL (SINOVA), 2024)
The aim of this research is to find out how to use methods to increase students' understanding in Islamic Religious Education learning regarding procedures for caring for corpses at State High School 1 North Sangatta. The type of research used is descriptive research. The approach in this research is a qualitative research approach. Data collection techniques in this research are observation, interviews and documentation. Meanwhile, the data analysis technique used in this research is the Miles and Huberman analysis technique, namely data condensation, data presentation, and drawing conclusions/data verification. Based on the results of this research, it shows that the use of efficiency methods in material on procedures for caring for corpses at State High School 1 North Sangatta is very effective because students can understand and put into practice what has been conveyed directly by the teacher and the use of efficiency methods makes learning more active. The inhibiting factor that influences the use of the roasting method is that the time specified is not enough to demonstrate the procedures for caring for the corpse as a whole. The solution given is that the teacher can summarize several procedures for caring for corpses.